Efficient oxygen reduction catalysis by subnanometer Pt alloy nanowires - Jiang, Kezhu (Sci Adv, 2017)
The common knowledge is that Pt and Pt alloy nanoparticles (NPs) less than 2 nm are not desirable for oxygen reduction reaction (ORR). However, whether the same trend is expected in Pt-based nanowires (NWs) and nanoplates remains questionable because there is no scalable approach to make such Pt nanostructures. We report a general approach for preparing subnanometer Pt alloy NWs with a diameter of only 4 to 5 atomic layer thickness, ranging from monometallic Pt NWs to bimetallic PtNi and PtCo NWs and to trimetallic PtNiCo NWs. In a sharp contrast to Pt alloy NPs, the subnanometer Pt alloy NWs demonstrate exceptional mass and specific activities of 4.20 A/mg and 5.11 mA/cm(2) at 0.9 V versus reversible hydrogen electrode (RHE), respectively, 32.3 and 26.9 times higher than those of the commercial Pt/C. Density functional theory simulations reveal that the enhanced ORR activities are attributed to the catalytically active sites on high-density (111) facets in the subnanometer Pt alloy NWs. They are also very stable under the ORR condition with negligible activity decay over the course of 30,000 cycles. Our work presents a new approach to maximize Pt catalytic efficiency with atomic level utilization for efficient heterogeneous catalysis and beyond.